Identifying anthropogenic and fixed influencing factors of shrub encroachment in Cypress Upland, Canada - Irini Soubry; Larissa Robinov; Thuan Chu; Xulin Guo (Heliyon, 2025)
When shrub cover in a grassland surpasses a critical threshold, it can alter the ecosystem negatively, leading to loss of grassland species and habitat, risk of high intensity fires, and loss of available forage for grazing. Shrub expansion into grasslands is a global issue and there is no solid conclusion for what is influencing it. This study aims to i) investigate anthropogenic factors that are connected to shrub cover; and ii) apply a model that uses topo-edaphic and anthropogenic factors to define current factors of shrub presence. Shrub cover in the study area (the West Block of the Saskatchewan Cypress Hills Interprovincial Park) has significantly extended into the native fescue grassland. Within the park, anthropogenic factors, such as closeness to roads, and time since last haying were connected to high shrub cover. When using topo-edaphic and anthropogenic variables in variations of generalized least squares models, a combination of distance to roads and hydrological features, high elevation, lack of haying, and certain soil moisture regimes and landscape units were connected to high shrub cover. The topo-edaphic factors were consistent with the literature and relate to the preferences of shrubs towards moisture, which is generated in the micro-climate from soil type, topography, elevation, and aspect. These are usually stable factors. Contrarily, anthropogenic factors vary over time and have a significant influence on shrub cover in the park. This research can be the steppingstone for achieving long-term resilience and sustainability of native grassland species and their habitats by better understanding the interaction of local factors on shrub presence.